If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(4n + -6) + -2n = -7n + 17 Reorder the terms: -6(-6 + 4n) + -2n = -7n + 17 (-6 * -6 + 4n * -6) + -2n = -7n + 17 (36 + -24n) + -2n = -7n + 17 Combine like terms: -24n + -2n = -26n 36 + -26n = -7n + 17 Reorder the terms: 36 + -26n = 17 + -7n Solving 36 + -26n = 17 + -7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7n' to each side of the equation. 36 + -26n + 7n = 17 + -7n + 7n Combine like terms: -26n + 7n = -19n 36 + -19n = 17 + -7n + 7n Combine like terms: -7n + 7n = 0 36 + -19n = 17 + 0 36 + -19n = 17 Add '-36' to each side of the equation. 36 + -36 + -19n = 17 + -36 Combine like terms: 36 + -36 = 0 0 + -19n = 17 + -36 -19n = 17 + -36 Combine like terms: 17 + -36 = -19 -19n = -19 Divide each side by '-19'. n = 1 Simplifying n = 1
| y-4=6 | | h+4/9=7/9 | | 7.4+d=-18.62 | | m-9.78=65.32 | | 6.3+k=12.5 | | b/4+10=13 | | 16+2a=-2(3a-4) | | 11-4x=6+x | | 4c+0=48 | | 3g-1+2g+8=g+2 | | A=5i+7j | | u+6=v | | -5+3x+3+2= | | -2(7-4)+4=-4 | | 7a=15a-80 | | 15y-12y=24 | | 0.02=100 | | 20y^7v^8u^2= | | 3(-2+x)=-24 | | 2b-6-3b-b= | | 10+7x=5x-6 | | (2x-1)(x+3)=(x-3)(x+1) | | 3x+21=68 | | -72-11c+6c^2=0 | | -4-5=3-3x+4x | | -2x-1=-(2x+3) | | -17+8v=-6v-5(2-3v) | | 32-4(6)(42)=0 | | 2x^2+4x-21=24-9x | | 9x-7=2x+3 | | 12(x+13)=252 | | 3+m+(-1m)= |